‘Facebook is the Devil’: Exploring Officer Perceptions of Cyber-based Harms Facing Youth in Rural and Remote Communities - Adorjan, Michael; Ricciardelli, Rosemary; Huey, Laura (International Journal of Rural Criminology, 2022)
Policing research, still largely concentrated on urban contexts, is increasingly recognizing the unique features of police work in rural regions. Beyond notable differences such as lower overall levels crime and fewer (though more sporadically distributed) people, little is also known regarding rural police understandings and responses to online mediated harms, including relatively serious forms of cyberbullying, non-consensual ‘sexting’, and other forms of crime mediated online. Interviews with police officers (N = 42) here focus on their views regarding police work in response to cyber-mediated harm facing youth in rural and remote Atlantic Canada. Responses center on how rural regions play a role in mediating the nature of online conflict and police respond to such conflict. Officers highlight several related challenges, such as lack of parental support, and how some youth ‘define deviancy down’, referring to a lack of recognition regarding the harm caused by cyberbullying and non-consensual sexting (including issues related to the distribution of child pornography). Implications are discussed for research on rural policing where evidence-based practices remain lacking.